A single-ended protection scheme for the hybrid MTDC power grid using traveling wave peak-to-decline ratio - Zijiang Wang; Zhaoyi Zhang; Jianbin Fan; Xinyue Zheng; Youping Fan (International Journal of Electrical Power & Energy Systems)
For multi-terminal HVDC(MTDC) power grids, boundary elements may not exist at the transmission line terminal, which makes traditional traveling wave protection schemes unsuitable. Furthermore, most traveling wave protection schemes require a high sampling frequency to detect the traveling wave heads and are not sensitive to the high-resistance ground fault. To solve these problems, a single-ended protection scheme using the traveling wave peak-to-decline ratio is proposed in this research. The 1-mode traveling wave propagation characteristics of different measuring points are first analyzed. Then, the peak-to-decline ratio and the change value of the 1-mode traveling wave are applied to construct the fault line identification criterion at the end of the DC line and the common point between two DC lines, respectively. Finally, the proposed protection scheme is verified by a hybrid three-terminal HVDC power grid. Results show that the proposed protection scheme only requires a 10 kHz sampling frequency, and the ground fault with 800 Ω fault resistance or 40 dB noise interference can be identified correctly.